Total hepatic inflow occlusion vs. hemihepatic inflow occlusion for laparoscopic liver resection: a systematic review and meta-analysis - An, Ting; Liu, Jie; Feng, Liwei (Frontiers in Surgery, 2024)
The control of bleeding during laparoscopic liver resection (LLR) is still a focus of research. However, the advantages of the main bleeding control methods, including total hepatic inflow occlusion (TIO) vs. hemihepatic inflow occlusion (HIO), during LLR remain controversial. The purpose of this meta-analysis was to compare the clinical outcomes of patients who received TIO and patients who received HIO. This meta-analysis searched the Medline, PubMed, Web of Science, Embase, Ovid, and Cochrane Library databases. The language of the studies was restricted to English, and comparative studies of patients treated with TIO and HIO during LLR were included. The primary outcome was to compare the intraoperative details, such as the operative time, occlusion time, and volume of blood loss, between the two groups. Secondary outcomes included conversion, overall complications, liver failure, biliary leakage, ascites, pleural effusion, and hospital stay. Five studies including 667 patients, 419 (62.82%) of whom received TIO and 248 (37.18%) of whom received HIO, were included in the analysis. The demographic data, including age, sex, hemoglobin, total bilirubin, albumin, and alpha-fetoprotein, were comparable. No significant differences noted in operative time, occlusion time, volume of blood loss, conversion, overall complications, liver failure, biliary leakage, hemorrhage, ascites, or pleural effusion. The hospital stay in patients who received HIO was significantly shorter than that for patients who received TIO [mean difference (MD), 0.60; 95% confidence interval (CI), 0.33–0.87; p < 0.0001; I2 = 54%]. The blood loss of patients with liver cirrhosis in the TIO group was significantly less than that in the HIO group (MD, −107.63; 95% CI, −152.63 to −62.63; p < 0.01; I2 = 27%). Both the TIO and HIO methods are safe and feasible for LLR. Compared with HIO, TIO seems to have less blood loss in cirrhotic patients. However, this result demands further research, especially multicenter randomized controlled trials, for verification in the future.Systematic Review Registration:https://www.crd.york.ac.uk/, Identifier PROSPERO (CRD42022382334).